Answer:
Explanation:
Recognize that this is the exponential function y = e^x with some tweaks:
f(x) = 2e^x + 1, as compared to y = e^x.
y = e^x is a basic function that we all should know well. Its graph looks much like the graph shown as "Part A." The graph starts in Quadrant II, crosses the y-axis into Quadrant I, and then continues growing rapidly as x increases.
As x => positive infinity, y => positive infinity. This is true of f(x) = 2e^x + 1 also.
As x => negative infinity, y => 0 (speaking of y = e^x).
As x => positive infinity, f(x) = 2e^x + 1 => positive infinity, in Quadrant I.